2021
DOI: 10.1017/s0033291721002245
|View full text |Cite
|
Sign up to set email alerts
|

Non-suicidal self-injury among first-year college students and its association with mental disorders: results from the World Mental Health International College Student (WMH-ICS) initiative

Abstract: Background Although non-suicidal self-injury (NSSI) is an issue of major concern to colleges worldwide, we lack detailed information about the epidemiology of NSSI among college students. The objectives of this study were to present the first cross-national data on the prevalence of NSSI and NSSI disorder among first-year college students and its association with mental disorders. Methods Data come from a survey of the entering class in 24 colleges across nine countries participating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 76 publications
3
51
0
Order By: Relevance
“…Interestingly, other substance use behavior did not affect the risk for frequent NSSI, though depression and anxiety increased the odds of frequent self-injurious behavior as expected. Although the temporal relationship between NSSI and substance use was unable to be assessed in the current study, a prior investigation of first-year college and university students suggested that the onset of a substance use disorder occurred more frequently after the onset of NSSI, compared to before NSSI onset ( 28 ). Thus, additional research on the motivations for e-cigarette use and the timing of use in relation to NSSI is necessary to advance the clinical relevance of future work in this field.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, other substance use behavior did not affect the risk for frequent NSSI, though depression and anxiety increased the odds of frequent self-injurious behavior as expected. Although the temporal relationship between NSSI and substance use was unable to be assessed in the current study, a prior investigation of first-year college and university students suggested that the onset of a substance use disorder occurred more frequently after the onset of NSSI, compared to before NSSI onset ( 28 ). Thus, additional research on the motivations for e-cigarette use and the timing of use in relation to NSSI is necessary to advance the clinical relevance of future work in this field.…”
Section: Discussionmentioning
confidence: 83%
“…Approximately one in five (19.8%) college students in the United States (US) endorse past-12 month NSSI ( 25 ); pooled lifetime prevalence among adults between 18 and 24 years is slightly lower (13.4%) ( 26 ). While NSSI is highly heterogeneous in type, frequency, and severity ( 27 ), the behavior has been identified as a strong predictor of poor mental health outcomes, including stress, anxiety, and emotional dysregulation ( 28 , 29 ). NSSI during adolescence increases the risk of attempting suicide during adulthood ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsuicidal self‐injury (NSSI) occurs in approximately 3%–6% of the adult general population (Klonsky, 2011; Liu, 2021; Plener et al, 2016; Swannell et al, 2014), 17%–27% of adolescents (Monto et al, 2018; Swannell et al, 2014; Zetterqvist et al, 2021), 13%–18% of young adults (Kiekens et al, 2021; Swannell et al, 2014), and up to 80% of clinical populations (Auerbach et al, 2014; Clarkin et al, 1983; Gunderson & Ridolfi, 2001). In addition to being associated with functional impairment and numerous psychiatric disorders (e.g., depression, posttraumatic stress disorder [PTSD], borderline personality disorder [BPD]; Bentley et al, 2015; Gratz et al, 2015; Patel et al, 2021), NSSI is a robust predictor of suicidal thoughts and behaviors (Asarnow et al, 2011; Franklin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsuicidal self-injury (NSSI; intentional damage of body tissue without suicidal intent) is a problem worldwide, affecting around 18% of adolescents and young adults during the life-time, with past year rates estimated to range from 8% to 18% [ 21 , 46 , 34 ]. Despite knowledge that NSSI commonly begins in adolescence (12–14 years-of-age; [ 51 , 62 ]) attention to how developmental phenomena, like identity and self-concept, may contribute to NSSI risk, are understudied [ 11 , 18 , 72 ].…”
Section: Introductionmentioning
confidence: 99%